Oil spill hazard from dispersal of oil along shipping lanes in the Southern Adriatic and Northern Ionian Seas. Issue 1 (15th January 2015) - Liubartseva, S.; De Dominicis, M.; Oddo, P.; Coppini, G.; Pinardi, N.; Greggio, N.
Highlights: New methodology of hazard mapping for operational oil spills was developed. UNESCO hazard definition was used in oil spill modelling. Mediterranean Forecasting System service was combined with ship traffic data. Hazard maps in the Southern Adriatic and Northern Ionian Seas were obtained. Abstract: An assessment of hazard stemming from operational oil ship discharges in the Southern Adriatic and Northern Ionian (SANI) Seas is presented. The methodology integrates ship traffic data, the fate and transport oil spill model MEDSLIK-II, coupled with the Mediterranean Forecasting System (MFS) ocean currents, sea surface temperature analyses and ECMWF surface winds. Monthly and climatological hazard maps were calculated for February 2009 through April 2013. Monthly hazard distributions of oil show that the zones of highest sea surface hazard are located in the southwestern Adriatic Sea and eastern Ionian Sea. Distinctive "hot spots" appear in front of the Taranto Port and the sea area between Corfu Island and the Greek coastlines. Beached oil hazard maps indicate the highest values in the Taranto Port area, on the eastern Greek coastline, as well as in the Bari Port area and near Brindisi Port area.